Report of the Indian Mercantile Marine Committee 1923-24 - Planning Commission (Planning Commission, 1923)
We propose to deal first with the question of the training of the executive or deck officers and subsequently with the training of engineers. In our opinion no scheme for the ultimate formation of an Indian Mercantile Marine would be complete unless it also provides both for the training and future employment of the officers. In Great Britain the officers of the Mercantile Marine are drawn chiefly from the middle classes. We are of opinion that it is necessary that a somewhat similar method of recruitment should also hold good in India if a thoroughly efficient sea service is to be created.
Report
Report